Impact of COVID-19 outbreak on the mental health in sport and among society - Kędra, Kamila; Michalik, Izabela; Zarańska, Julia; Aab, Arkadiusz; Bielak, Maciej (Journal of Education, Health and Sport, 2023)
The COVID-19 pandemic has had a significant impact on global mental health, affecting individuals of all age groups and various demographic backgrounds including athletes. Anxiety disorders have become more prevalent during the pandemic, attributed to factors such as quarantine, social isolation, fear of the virus, job insecurity, and the psychological impact of a pandemic. This narrative review aims to summarize the existing literature addressing mental health issues related to the COVID-19 pandemic, as well as the associated risk factors and potential interventions. Additionally, the review explores the impact of COVID-19 on specific populations, including athletes, frontline healthcare workers, children and adolescents, and individuals with pre-existing mental health conditions. In addition, the review explores the long-term consequences of the pandemic on mental health, including the potential for a surge in post-traumatic stress disorder (PTSD) and other trauma-related disorders. Overall, this review underscores the urgent need for comprehensive mental health support and resources in response to the COVID-19 pandemic.